Pengaruh PDRB, Upah Minimum, Investasi Terhadap Penyerapan Tenaga Kerja di Provinsi Jawa Timur - Rahmatuz Zainiya Salsabilla; Tony Seno Aji (Universitas Negeri Surabaya, 2025)
East Java Province as one of the regions with the highest economic growth in Indonesia has great potential in employment. This study aims to determine the effect of GRDP, Minimum Wage and Investment on employment in 38 cities / regencies in East Java Province in 2017-2023. The method used in this study is quantitative correlation with panel data regression with the Fixed Effect Model (FEM) approach. The results of this study indicate that GRDP, Minimum Wage and Investment simultaneously affect employment in East Java Province. Partially, GRDP and Minimum Wage have a positive and significant effect on employment in East Java Province, while the Investment variable has a negative and insignificant effect on employment in East Java Province.